(untitled) (Innovative professional education, 2024)
The subsection deals with current approaches and methods of developing pedagogical skills of teachers of general education disciplines in vocational (vocational-technical) education institutions. Particular attention is paid to the issues of improving the professional competences of teachers through the introduction of innovative technologies, digital tools and methods of active learning.